Reorientation of School-Based Curriculum Management to Support the Deep Learning Ecosystem in Elementary Schools - Avisina Anadri; Hendardi Rizaldi; Irvan Trisno Trisno Susandi; Rusmal Kahvi; Popi Puadah; Madian Muhammad Muchlis (Al-Ulum: Jurnal Pendidikan Islam, 2026)
Curriculum transformation toward deep learning is often hampered by school management that remains administratively linear. This study aims to analyze strategies for reorienting curriculum management in elementary schools to support a deep learning ecosystem that focuses on essential material and character (6C). The method used was a systematic literature review of policy documents and reputable scientific articles for the 2021-2026 period. Data were analyzed using thematic techniques to identify patterns of management paradigm shifts. The results indicate that schedule flexibility, strengthening professional learning communities, and optimizing technology are key pillars of successful transformation. These findings emphasize the need for a management paradigm shift from "content completion" to "competency mastery" to improve student literacy and numeracy. The implications of this research emphasize that managerial autonomy at the educational unit level is an absolute prerequisite for successful curriculum implementation in elementary schools.